A novel mutation in SPART gene causes a severe neurodevelopmental delay due to mitochondrial dysfunction with complex I impairments and altered pyruvate metabolism. Issue 10 (7th August 2019) - Diquigiovanni, Chiara; Bergamini, Christian; Diaz, Rebeca; Liparulo, Irene; Bianco, Francesca; Masin, Luca; Baldassarro, Vito Antonio; Rizzardi, Nicola; Tranchina, Antonia; Buscherini, Francesco; Wischmeijer, Anita; Pippucci, Tommaso; et al.
ABSTRACT: Loss‐of‐function mutations in the SPART gene cause Troyer syndrome, a recessive form of spastic paraplegia resulting in muscle weakness, short stature, and cognitive defects. SPART encodes for Spartin, a protein linked to endosomal trafficking and mitochondrial membrane potential maintenance. Here, we identified with whole exorne sequencing (WES) a novel frameshift mutation in the SPART gene in 2 brothers presenting an uncharacterized developmental delay and short stature. Functional characterization in an SH‐SY5Y cell model shows that this mutation is associated with increased neurite outgrowth. These cells also show a marked decrease in mitochondrial complex I (NADH dehydrogenase) activity, coupled to decreased ATP synthesis and defective mitochondrial membrane potential. The cells also presented an increase in reactive oxygen species, extracellular pyruvate, and NADH levels, consistent with impaired complex I activity. In concordance with a severe mitochondrial failure, Spartin loss also led to an altered intracellular Ca 2+ homeostasis that was restored after transient expression of wild‐type Spartin. Our data provide for the first time a thorough assessment of Spartin loss effects, including impaired complex I activity coupled to increased extracellular pyruvate. In summary, through a WES study we assign a diagnosis of Troyer syndrome to otherwise undiagnosed patients, and by functional characterization we show that the novel mutation in SPART leads to a profound bioenergetic imbalance.—Diquigiovanni, C., Bergamini, C., Diaz, R., Liparulo, I., Bianco, F., Masin, L., Baldassarro, V. A., Rizzardi, N., Tranchina, A., Buscherini, F., Wischmeijer, A., Pippucci, T., Scarano, E., Cordelli, D. M., Fato, R., Seri, M., Paracchini, S., Bonora, E. A novel mutation in SPART gene causes a severe neurodevelopmental delay due to mitochondrial dysfunction with complex I impairments and altered pyruvate metabolism. FASEB J. 33, 11284–11302 (2019). www.fasebj.org